(untitled) - Heinzel, Thomas (Weinheim, 2007)
This book treats electronic transport in the regime including the effect of electronic phase coherence, energy quantization and single-electron charging. This edition is completely updated and expanded, and now comprises new chapters on spin electronics and quantum information processing, transport in inhomogeneous magnetic fields, organic/molecular electronics, and applications of field effect transistors. The book also provides an overview of semiconductor processing technologies and experimental techniques
Keywords: Mesoscopic phenomena (Physics),Nanostructures,Cấu trúc Nano